Some Types of Tri-Locally Compactness Spaces (European Journal of Pure and Applied Mathematics, 2025)
In this study, the locally compactness spaces property will be investigated for three topologies, known as tri-locally compact spaces. Additionally, the features of these spaces will be investigated in terms of locally compact spaces. Many theoretical results have been presented and proven, and several well-known theorems concerning locally compact spaces have been extended to apply to three topologies. An illustrative example is provided to support the findings.